1993
DOI: 10.1128/mcb.13.1.289
|View full text |Cite
|
Sign up to set email alerts
|

Direct selection for mutations affecting specific splice sites in a hamster dihydrofolate reductase minigene.

Abstract: A Chinese hamster cell line containing an extra exon 2 (50 bp) inserted into a single intron of a dihydrofolate reductase (dhfr) minigene was constructed. The extra exon 2 was efficiently spliced into the RNA, resulting in an mRNA that is incapable of coding for the DHFR enzyme. Mutations that decreased splicing of this extra exon 2 caused it to be skipped and so produced normal dhfr mRNA. In contrast to the parental cell line, the splicing mutants display a DHFR-positive growth phenotype. Splicing mutants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 85 publications
(101 reference statements)
4
48
0
Order By: Relevance
“…Exon 2+3 with its splice consensus sequences was replaced by a NotI site to serve as an insertion site for heterologous exons. Thus, the sequences surrounding the NotI insertion site in the test exon retain the original dhfr flanks, including the branch point of intron 1 at ‫42מ‬ (Chen and Chasin 1993). The experiment was designed in this way to increase the chance of revealing sequences or sequence relationships that influence splicing over and above the presence of a functional branch site; a similar consideration applies to the downstream flank; the flank deletion experiments here are testing for effects that cannot be fulfilled by any ISEs that might be present in the original dhfr flank.…”
Section: Resultsmentioning
confidence: 99%
“…Exon 2+3 with its splice consensus sequences was replaced by a NotI site to serve as an insertion site for heterologous exons. Thus, the sequences surrounding the NotI insertion site in the test exon retain the original dhfr flanks, including the branch point of intron 1 at ‫42מ‬ (Chen and Chasin 1993). The experiment was designed in this way to increase the chance of revealing sequences or sequence relationships that influence splicing over and above the presence of a functional branch site; a similar consideration applies to the downstream flank; the flank deletion experiments here are testing for effects that cannot be fulfilled by any ISEs that might be present in the original dhfr flank.…”
Section: Resultsmentioning
confidence: 99%
“…4) (44). Additional constructs with variations characterized as splicing mutations in prior reports (45) were designed as sensitized reporters. Inserts were selected on the basis of their match to the cluster motif.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the induction of exon skipping was not caused by the mere introduction of a foreign sequence. We have previously shown that the insertion of much larger sequences (>100 nt) does not usually compromise splicing (Chen and Chasin 1994;Fairbrother and Chasin 2000). Interestingly, one of the two PESSs that did not inhibit splicing as a single copy, PS12, constitutes a CACACACA repeat-a sequence that has been characterized as an intronic enhancer (Hui et al 2003).…”
Section: Testing Putative Exonic Splicing Silencersmentioning
confidence: 99%